1991
DOI: 10.1111/j.1365-2265.1991.tb03501.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic blockade with pirenzepine induces dose‐related reduction in glucose and insulin responses to a mixed meal in normal subjects and non‐insulin dependent diabetics

Abstract: Improvement in carbohydrate tolerance after pirenzepine in normal subjects is dose related and largely independent of GH suppression. Cholinergic blockade can also improve meal carbohydrate tolerance with simultaneous reduction in plasma insulin concentrations in non-insulin dependent diabetics, particularly those with obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
13
2
Order By: Relevance
“…Furthermore, it has been proposed that insulin resistance in patients with non-insulin-dependent diabetes and hepatic diseases may be accounted for by hepatic parasympathetic neuropathy (Lautt, 1979). In contrast, it has been reported that cholinergic blockade with pirenzepine produced an improvement of glu-cose tolerance in normal human and noninsulin dependent diabetics (Bevan et at., 1991). The main objective of this study was to investigate the influence of muscarinic cholinergic blockade on insulin sensitivity, and to assess possible alterations in the endogenous pancreatic hormones produced by this blockade.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been proposed that insulin resistance in patients with non-insulin-dependent diabetes and hepatic diseases may be accounted for by hepatic parasympathetic neuropathy (Lautt, 1979). In contrast, it has been reported that cholinergic blockade with pirenzepine produced an improvement of glu-cose tolerance in normal human and noninsulin dependent diabetics (Bevan et at., 1991). The main objective of this study was to investigate the influence of muscarinic cholinergic blockade on insulin sensitivity, and to assess possible alterations in the endogenous pancreatic hormones produced by this blockade.…”
Section: Introductionmentioning
confidence: 99%
“…Somatostatin reduces insulin but decreases glucose tolerance in patients with PCOS (Prelevic et al, 1990). In contrast, pirenzepine (PIR), a muscarinic cholinergic antagonist, reduces both insulin and glucose responses to food in normal individuals and patients with non-insulin dependent diabetes mellitus (Page et al, 1989;Bevan et al, 1991). We have therefore studied the dose related actions of PIR on insulin and glucose in response to food in obese clinically hyperandrogenic women with PCOS.…”
mentioning
confidence: 99%
“…We anticipated that muscarinic blockade would have at least a modest effect on gastric emptying based on previously published studies (8,33). Indeed, because of the importance of vagal innervation in the control of gastric motility, blockade of either muscarinic or nicotinic signaling is expected to retard gastric emptying and therefore the delivery of nutrients to the absorptive surface of the small intestine.…”
Section: Discussionmentioning
confidence: 99%